Free vibration analysis of aluminum foam metal sandwich panels: a comparative study between numerical and analytical modelling - Zahra Hamdan; Sadeq Bakhy; Muhsin Jweeg (Engineering and Technology Journal)
This study investigates the natural frequencies and vibrational behavior of aluminum foam sandwich panels by using numerical and analytical methods. The panels consist of an aluminum foam core sandwiched between two aluminum sheets, offering a lightweight yet structurally robust solution, making them ideal for applications in the aerospace and automotive industries. A mathematical model based on classical plate theory (CPT) was developed to compute the natural frequencies of supported rectangular sandwich plates. The Gibson-Ashby equation was employed to estimate the Young's modulus of the aluminum foam core. The analytical model was validated using finite element analysis (FEA) conducted in ANSYS 2021 R1, allowing for a thorough comparison between numerical and analytical results. The results showed strong agreement between the numerical and theoretical analysis, especially at high foam densities. The discrepancies between the numerical simulation and analytical predictions decreased with increasing foam density. For instance, at a density of 850 kg/m³, the difference between the numerical natural frequency (674 Hz) and the analytical prediction (681.75 Hz) was only 1.14%. In contrast, at a lower density of 350 kg/m³, the discrepancy increased to 8.52%, with numerical and analytical frequencies of 739.66 Hz and 808.51 Hz, respectively. This trend can be attributed to the complexities in the material behavior at lower densities, which the analytical model simplifies by neglecting nonlinear deformations and complex stress distributions. As foam density increases, the material exhibits more consistent mechanical properties, resulting in closer alignment between numerical and analytical results. Moreover, higher foam densities contribute to an increase in mass, which negatively affects the natural frequency, causing it to decrease. Conversely, an increase in Young's modulus enhances the stiffness of the material, resulting in higher natural frequencies. Therefore, the optimal foam density range of 350 to 450 kg/m³ is crucial for achieving a good balance between stiffness and weight. Maintaining a lightweight structure while improving stiffness is essential for achieving optimal performance. Consequently, these panels are particularly suitable for applications in the aerospace and automotive sectors that require lightweight, high-performance structures.